한국어 인식론적 범주의 안과 밖 - 박재연 (언어학, 2018)
The aims of this paper are to examine the range of Korean epistemological categories especially evidentiality and assimilation(mirativity), and to consider some problems in describing the meaning of Korean endings. Firstly, I reexamine the view that Korean connective endings ‘-gillae, -eunigga’ and ‘-ja’ express the evidential property of ‘perception’. While ‘-gillae’ has exactly the same syntactic or semantic properties as those of typical evidentials, ‘-eunigga’ and ‘-ja’ have different properties from evidential forms. Therefore it is inappropriate that ‘-eunigga’ and ‘-ja’ are treated as evidential items. Secondly, I discuss the similarity and difference between the property of assimilation and so-called ‘relation of the scene of utterance.’ Strictly the characteristics of Korean mirative endings ‘-ne’ and -deo-’ are different from those of ‘-gess-’ that is related to the scene of utterance. Finally, I consider some problems in describing the meaning of Korean endings. I insist that the meaning of Korean endings could be polysemous and complex and the realization of semantic components of epistemological meanings could have some hierarchy and variability.
Keywords: epistemological categories; evidentiality; assimilation/mirativity; relation of the scene of utterance; semantic components; polysemy; complexity; hierarchy; variability